Application of genetic algorithmbin an active noise control system - BATKO, Wojciech; FELIS, Józef; FLACH, Artur; KAMISIŃSKI, Tadeusz; GIESKO, Tomasz; ZBROWSKI, Andrzej (Archives of Acoustics, 2008)
Automation of acoustic measurements constitutes a considerable challenge to designers. On one hand, the special character of acoustic measurements in an anechoic room requires designs that minimize disturbances to the acoustic field; on the other hand, automation always involves the introduction of additional mechanical elements, which disturb this field. The authors of this paper attempt to reconcile these conflicting demands by designing a mechatronic measurement system. On the basis of known solutions and current measurement needs, a number of concepts has been proposed, and a design has been identified that can be implemented in the room under study.